Melestarikan Gordang Sambilan sebagai Simbol Kearifan Lokal : Program Kerja KKN di Desa Pangkat Kecamatan Lembah Sorik Marapi - Yusril Mahendra; Wahyuni Daulay; Juli Avni Siregar; Siti Khodijah; Nurul Fatma Hidayah; Nur Hakikah; Riska Yulia; Rosdanilah Rosdanilah; Afrizal Afrizal; Haddad Ulum Harahap (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service Program (KKN) is one of the important ways of serving the community in preserving local culture. This activity was carried out in Pangkat Village, Lembah Sorik Marapi Subdistrict, with the aim of safeguarding Gordang Sambilan as a symbol of Mandailing local wisdom. The program sought to raise awareness among the community, especially the younger generation, about the philosophical, spiritual, and social values embedded in Gordang Sambilan, while also encouraging the emergence of a new generation of traditional art performers. The method applied combined a participatory-collaborative approach with educational and cultural strategies, along with the Asset-Based Community Development (ABCD) model. The stages of the program included preparation, socialization, cultural performances, and basic training. The results showed increased community participation, strong enthusiasm among the younger generation to practice, and support from village officials and cultural leaders. This program demonstrates that active intergenerational involvement through direct practice can strengthen Mandailing cultural identity and open opportunities for the development of culture-based tourism.